2016
DOI: 10.1111/jmft.12157
|View full text |Cite
|
Sign up to set email alerts
|

Therapist Differentiation and Couple Clients' Perceptions of Therapeutic Alliance

Abstract: Therapeutic alliance has been acknowledged as one of the catalysts for change within a therapeutic relationship. The contributions of therapists' characteristics to alliance are not often studied. From a Bowen System's Theory perspective, the therapist's level of differentiation would be highly relevant to the development of a therapeutic alliance. The hypothesis for this study was that therapists who are able to take a more differentiated stance in therapy will build a stronger therapeutic alliance. To test t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…The results of the study showing that therapist gender was not a significant predictor of therapist effects is consistent with previous couple therapy research (Bartle‐Haring et al, 2016; Owen et al, 2014). In addition, this study found that therapist experience was not a significant predictor of therapist effects in couple therapy.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results of the study showing that therapist gender was not a significant predictor of therapist effects is consistent with previous couple therapy research (Bartle‐Haring et al, 2016; Owen et al, 2014). In addition, this study found that therapist experience was not a significant predictor of therapist effects in couple therapy.…”
Section: Discussionsupporting
confidence: 90%
“…The researchers found that therapist variables were one of the model‐independent themes that contributed to successful outcomes, suggesting that attributes of the therapist were an important ingredient in successful MFT therapy. In a study of nine therapists and 93 couples, Bartle‐Haring et al (2016) found that 4% of variability of the couple bond dimension of the therapeutic alliance over the first six sessions was attributed to the therapist. However, as part of the preliminary analysis in a study of the therapeutic alliance and dropout in individual, couple, and family therapy, authors of another study found that there were no significant therapist effects in the therapeutic alliance after one session (Anderson et al, 2019).…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…More highly differentiated health professionals might better enable clients to develop healthy ways of relating in the face of stress, thereby improving client psychological and physical well‐being. This area is rarely researched, and future studies should clarify inconsistent empirical findings on if and how the therapist's differentiation benefits the therapeutic relationship and client outcomes (Bartle‐Haring, Shannon, Bowers, & Holowacz, ; Lambert & Friedlander, ).…”
Section: Discussionmentioning
confidence: 99%
“…There are other nuances and issues that need to be understood in MLM analyses that go beyond this primer as well. We invite the reader to explore articles that have been published that use MLM such as Bartle‐Haring, Shannon, Bowers and Holowacz (2016), Bartle‐Haring, Knerr, Adkins, et al (2012), Lyons and Sayer (2005), and Sevier, Atkins, Doss, and Christensen (2015).…”
Section: Discussionmentioning
confidence: 99%